'A Cornish Voice in the Celtic Orchestra': Robert Morton Nance and the Celtic Congress of 1926. (1st May 2008) - Williams, Derek R.
The subject of where the fledgling Celtic Congress should be held each year - and, more specifically, the venue for the proposed 1926 Congress, was one of contention. Using the extensive correspondence housed in the National Library of Wales, between such Celtic luminaries as Edward T. John, D. Rhys Phillips, Robert Morton Nance, Agnes O'Farrelly and a number of lesser players, this article examines how, inspired by Henry Jenner's early efforts to gain recognition for Cornwall as a Celtic nation, Robert Morton Nance was largely responsible for bringing her once again into the fold after the decline of Pan-Celticism during the war years of 1914-18. His efforts reflected the continuing deep-seated concern among Cornish revivalists that Cornwall be accepted by its sister nations as a bona fide Celtic country, one of the great preoccupations of the Cornish movement in the twentieth century. The staging of the Celtic Congress in Cornwall would be the outward and visible sign of Cornish Celticity and its acknowledgment by the other Celtic nations. Nance's aim, therefore, was to bring the Congress to Cornwall.